Temporal alteration of serum bilirubin levels and its renoprotective effects in diabetic kidney disease: exploring the hormonal mechanisms - Cao, Can; Wei, Shuwu; He, Leijuan; Li, Chunyao; Lu, Yizhen; Sun, Weiwei; Wang, Yaoxian (Frontiers in Endocrinology, 2024)
Objective: This current study represents a novel endeavor to scrutinize the correlation between the temporal alteration in serum total bilirubin (TBIL) concentrations and the rate of estimated glomerular filtration rate (eGFR). Additionally, this study aims to probe the plausible molecular mechanism underpinning the renoprotective effects of bilirubin concerning its hormonal characteristics.In this study, a cohort of 103 patients diagnosed with DKD and receiving medical care at Dongzhimen Hospital were recruited and monitored over a period of 2-7 years. The progression of DKD was ascertained using a threshold of eGFR decline > -5.48%/year. To assess the relationship between the annual change in serum TBIL levels (%/year) and the slope of eGFR, multivariate binary logistic regression analysis was employed. Furthermore, the ROC curve analysis was employed to determine the cut-off value for TBIL levels (%/year).Results: The use of multivariate binary logistic regression models revealed that serum TBIL levels (%/year) exhibited a significant correlation with the slope of eGFR. Moreover, the ROC curve analysis indicated a cut-off value of -6.729%/year for TBIL levels (%/year) with a sensitivity of 0.75 and specificity of 0.603, in diagnosing eGFR decline >-5.48 %/year.The findings of this study suggest that the sustained elevation of serum bilirubin concentration within the physiological range can effectively retard the progression of Diabetic Kidney Disease (DKD). Furthermore, the hormonal attributes of bilirubin may underlie its renoprotective effects.